Human Activity and State Policy Analysis on Aeolian Desertification in China - Wang, Tao; Zhou, Lihua; Yang, Guojing (Annals of Arid Zone, 2016)
Aeolian desertification is often caused by excessive human activities i Northern China. Excessive human activities are often caused by the unreasonable state p licies. The expansion of aeolian desertification in northern China during different histori al periods is related to the growth of human population and changes in state policy. Rapid expansion of population accelerated the reclamation of grasslands for farmlands, and so ccelerated the aeolian desertification process. Certain state policies encouraged the peasant to pursue short-term economic gain via over-grazing, over-cropping and over-logging in sate-owned lands, resulting in severe aeolian desertification. Nonetheless, in several typic~l areas in northern China, aeolian desertification has reversed during the past 5 years, ~ue to the application of new policies to reduce the human activities and to protect th ecological environment in these areas. Because human activities and state policies can d amatically change land-use patterns, abruptly destroy land cover within a short period, an accelerate aeolian desertification, analysis of human activities and the development of appropriate state policies are very important to combat aeolian desertification in China. I Key words: Aeolian Desertification, human activity, state policy, Northern china